Trial of exercise to prevent HypeRtension in young adults (TEPHRA) a randomized controlled trial: study protocol - Williamson, W; Huckstep, O; Frangou, E; Mohamed, A; Tan, C; Alsharqi, M; Bertagnolli, M; Lapidaire, W; Newton, J; Hanssen, H; McManus, R; Dawes, H; et al. (BioMed Central, 2018)
Background Hypertension prevalence in young adults has increased and is associated with increased incidence of cerebrovascular and cardiovascular events in middle age. However, there is significant debate regards how to effectively manage young adult hypertension with recommendation to target lifestyle intervention. Surprisingly, no trials have investigated whether lifestyle advice developed for blood pressure control in older adults is effective in these younger populations. Methods/Design TEPHRA is an open label, parallel arm, randomised controlled trial in young adults with high normal and elevated blood pressure. The study will compare a supervised physical activity intervention consisting of 16 weeks structured exercise, physical activity self-monitoring and motivational coaching with a control group receiving usual care/minimal intervention. Two hundred young adults aged 18–35 years, including a subgroup of preterm born participants will be recruited through open recruitment and direct invitation. Participants will be randomised in a ratio of 1:1 to either the exercise intervention group or control group. Primary outcome will be ambulatory blood pressure monitoring at 16 weeks with measure of sustained effect at 12 months. Study measures include multimodal cardiovascular assessments; peripheral vascular measures, blood sampling, microvascular assessment, echocardiography, objective physical activity monitoring and a subgroup will complete multi-organ magnetic resonance imaging. Discussion The results of this trial will deliver a novel, randomised control trial that reports the effect of physical activity intervention on blood pressure integrated with detailed cardiovascular phenotyping in young adults. The results will support the development of future research and expand the evidence-based management of blood pressure in young adult populations. Trial Registration Clinicaltrials.gov registration number NCT02723552, registered on 30 March, 2016.